Effect of codend mesh sizes on the size selectivity and exploitation pattern of cocktail shrimp (Trachypenaeus curvirostris) in shrimp trawl fishery of the South China Sea - Yang, Bingzhong; Herrmann, Bent (Frontiers in Marine Science, 2022)
In this study, we tested and compared the size selectivity and exploitation pattern of diamond-mesh codends, with mesh sizes ranging from 25 to 54 mm, for cocktail shrimp (Trachypenaeus curvirostris) in the South China Sea (SCS). Using the minimum mesh size (MMS) regulation of shrimp trawl fishery, 25 mm, as a starting point, we investigated how the mesh sizes used in the codends would affect the size selectivity and exploitation pattern, incorporating the minimum conservation reference size (MCRS, 7.0 cm total length) of cocktail shrimp in the SCS. Our results showed that the selective properties of the legal codend, with 25 mm mesh size, were not satisfactory for protecting juvenile individuals of cocktail shrimp. It obtained a L50 (50% retention length) of 5.85 cm (CI: 5.16-6.18 cm), far less than the MCRS of cocktail shrimp; the retention probability of a shrimp with a MCRS length was as high as 97.45 % (CI: 86.86-100.00%), and more than 40% of undersized shrimp was retained. Increasing the mesh sizes in the codend did not have significant effect on improving the size selectivity and exploitation pattern, implying other gear modifications are needed. Our study will be beneficial for the fishery management in the SCS.